Editorial - Mushtaqur Rahman (International Institute of Islamic Thought, 1988)
Five years of the American Journal of Islamic Social Sciences (AJISS) seem trivial, but there has been a good reason to seize upon this occasion as a brief respite from the here-and-now to look back at our objectives and accomplishments. It is gratifying that AJISS is now a lading journal of Islamic research published in United States, and a major international journal. It has published medium and longer length articles by scholars within and outside the United States, representing original, significant, and major Islamic conceptual and interpretative advances within all subfields of the social sciences. The articles have reflected the breadth, depth, and scale of modern Islamic scholarship, regardless of their perspectives and orientations. Among of the objectives of AJISS, and its sponsors, namely the International Institute of Islamic Thought (IIIT) and the Association of Muslim Social Scientists (AMSS), has been the effort to restore confidence among the Muslim scholars and revive Islamic scholarship to its former high standards. In addition there has been a modest effort to bring the ummah out of its present decadent situation and historic Nostalgic bonds. Ordinarily, such a situation develops when a nation starts living in memories and monuments, memorizes history and narrates it while ignoring or relegating the realities of the time. The other perspective of history, and perhaps more desirable, is when the people learn from history, interpret history and transform the present knowledge according to their history, values, and ethics. During the past five years, AJISS has persistently attempted to lead the way in fashioning a proper historical perspective by reverting to the basics, and by Islamizing the current knowledge. This issue begins with selections from the Holy Qur'an and commentary by 'AbdulHamid A. AbuSulayman. Three major sections follow. Section one includes two papers on the need and philosophy of Islamization of knowledge. In the first paper, Fazlur Rahman, presents his perspective on the Islamization of Knowledge and suggests modification of the present approach. The second paper by Ilyas By-Yunus gives a brief biography of Isma'il al Faruqi, and traces the development of his ideas of Islamization as one of the effective means for Muslim resurgence. The second section of this issue has three papers on matters concerning Islamic Thought. In the first, Louay Safi discusses war and peace in Islam, challenging the classical doctrines as issue-specific and incomprehensive. Arguing his case with credible support from other sources, Safi offers an alternative approach based on Islamic principles. The other paper by Abdulaziz Sachedena elaborates the importance of the Shari'ah by upholding the Tawhid principles in assimilating diverse groups with varied interests into one Ummah ...